Control interno a inventarios y su incidencia en la toma de decisiones de la empresa Exp e Imp Manobal c ltda. Cantón Quevedo, año 2022 - Cobeña Mera, Karelys Adelaida (2024)
The general objective of this research was to evaluate the internal control of inventories and its impact on the decision making of the company Exp e Imp. Manobal C Ltda., in the year 2022. The study was carried out through the pragmatic paradigm with mixed approach of non-experimental type and descriptive scope, which allowed the examination of existing inventory management and control practices, diagnosis of internal control using the COSO III model, application of financial indicators and analysis of the VNR. Among the findings found, it can be mentioned that although the company has an efficient Internal Control System, a high risk level is dominated by ignorance of control policies, followed by a medium risk level by the lack of function and procedure manuals; However, the VNR analysis was satisfactory and demonstrates that Manobal operates with solid and efficient inventory management, without the need for adjustments for impairment in the financial year investigated. Therefore, it is concluded that it is necessary to create internal policies and procedures for the effectiveness and reasonable security of the company's inventory management, in order to guarantee its implementation in the short and medium term; as well as.